1929
DOI: 10.1084/jem.49.3.461
|View full text |Cite
|
Sign up to set email alerts
|

The Separation of Types Among the Pneumococci Hitherto Called Group Iv and the Development of Therapeutic Antiserums for These Types

Abstract: The pneumococci hitherto known as Group IV have been separated into ten types which have been designated by Roman numerals from IV to XIII. These have been correlated as far as possible with the types described by others. The prevalence and mortality of cases due to each type have been estimated in the limited number of cases studied. Laboratory tests indicated that therapeutic antiserums for Types I, II and III have very little protective power against the recently separated types. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

1930
1930
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Variations shown for different strains were not confined to any one type. Possibly the inclusion of a larger number of the members of Group IV would show that these organisms have, as a class, a lesser growth capacity in normal human serum and leucocytes than the so-called fixed types, although the recent reclassification of Group IV and Type II atypical pneumococci by Cooper, Edwards and Rosenstein (5) indicates that a considerable percentage of these organisms are to be considered as highly pathogenic as the members of Types I, II, III.…”
Section: Discussionmentioning
confidence: 99%
“…Variations shown for different strains were not confined to any one type. Possibly the inclusion of a larger number of the members of Group IV would show that these organisms have, as a class, a lesser growth capacity in normal human serum and leucocytes than the so-called fixed types, although the recent reclassification of Group IV and Type II atypical pneumococci by Cooper, Edwards and Rosenstein (5) indicates that a considerable percentage of these organisms are to be considered as highly pathogenic as the members of Types I, II, III.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, 6A and 6B serotypes accounted for 4.6% and 10.6% of pneumococcal meningitis or sepsis in young children before the introduction of a pneumococcal conjugate vaccine (24). Extensive biochemical studies since their discovery in 1929 (7) have shown the 6A/6B PS to be isopolymers containing galactose-glucose-rhamnose-ribitol-phosphate, differing only in the rhamnose-ribitol linkage (12,22). Genetic studies of the capsule loci from many isolates showed that the capsule loci of 6A and 6B are largely identical and that only one nucleotide in wciP (G584A; S195N) is consistently different between the capsule loci of the two serotypes (16).…”
mentioning
confidence: 99%
“…Of the 5 preparations used, 4 were specific polysaccharides of types not previously tested in human subjects, namely Types IV, V, VII, and XIV (38), and the fifth was a Type I preparation. The local reactions to initial intracutaneous injections observed with all of these preparations were similar to those observed by Finland and Dowling (9) with the socalled cellular carbohydrates.…”
Section: Discussionmentioning
confidence: 99%